Feed production techniques using local raw materials for mud crab farmers in Madak Belek Hamlet, Sekotong District - Diamahesa, Wastu Ayu; Lumbessy, Salnida Yuniarti; Azhar, Fariq; Abidin, Zaenal; Badrun, Badrun; Affandi, Rangga Idris; Sumsanto, Muhammad; Diniariwisan, Damai; Rahmadani, Thoy Batun Citra; Setyono, Bagus Dwi Hari (Penamas: Journal of Community Service, 2025)
This community service activity focused on developing feed production techniques using local raw materials for mud crab farmers in Madak Belek Hamlet, Sekotong District. The main challenge faced by farmers is the high cost of commercial feed, which reduces profit margins. In fact, the area is rich in underutilized nutrient-rich local resources such as trash fish and seafood processing by-products. A participatory approach was applied, including observation, socialization, demonstration, hands-on training, and evaluation. The training emphasized feed formulation and the application of 5% wheat gluten as a binder, which had been proven in preliminary studies to enhance feed stability in water. The results showed an improvement in participants’ knowledge and skills in processing local ingredients into quality feed. The expected impacts include reducing dependence on commercial feed, lowering production costs, and improving the efficiency and sustainability of mud crab farming. For further optimization, feed performance testing on crab growth and economic feasibility analysis are required.